PERKEMBANGAN OVARIUM IKAN WADER PARI (Rasbora lateristriata Bleeker, 1854): PENDEKATAN HISTOLOGI - Zulfadhli Zulfadhli; Nastiti Wijayanti; Bambang Retnoaji (Universitas Teuku Umar, 2016)
This study was to determinte of development ovarian wader pari fish (Rasbora lateristriata) as part of the process of reproduction, which is the basic for information to R. lateristriata management. This study was done in october 2014 - april 2015 at Histology and Embryology Animal Laboratory of Gadjah Mada University. The object of the research was larva R. lateristriata with average weight of 0.02 grams. They were kept during 3 months. The result data of histology were analized and observed discussed descriptively. The results of observation showed that ovarian R. lateristriata indicated asincronous development patterns. The development of ovarian in the 1st month was at the chromatin nucleolar phase, while perinucleolar phase appeared in the 2nd and 3rd month.